2020
DOI: 10.2478/nuka-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of onco-epidemiological studies of the relationship between lung cancer and indoor radon exposure

Abstract: AbstractObjectives: Recent results of epidemiological and medical statistics studies of lung cancer and indoor radon in different regions of the world make a relevant new combined analysis of residential exposure health effects. In particular, new data were obtained by means of a meta-analysis of case-control studies as well as taking into account a confounding effect of human papillomavirus infection in studies of geographically aggregated data. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A strong causal association between residential radon exposure and lung cancer mortality is supported by pooled analysis of case control studies performed in Europe and North America [2,3]. A combined evaluation of estimates of residential case control studies meta-analysis and geographically aggregated data on lung cancer mortality and average indoor radon concentration yielded an excess risk of lung cancer of about 14% (90% CI: 0.10-0.18) per radon concentration 100 Bq/m 3 linked to an exposure period of 25-30 years [4]. The health risk assessment has demonstrated that radon is the second cause of cancer after smoking [1,5].…”
Section: Introductionmentioning
confidence: 97%
“…A strong causal association between residential radon exposure and lung cancer mortality is supported by pooled analysis of case control studies performed in Europe and North America [2,3]. A combined evaluation of estimates of residential case control studies meta-analysis and geographically aggregated data on lung cancer mortality and average indoor radon concentration yielded an excess risk of lung cancer of about 14% (90% CI: 0.10-0.18) per radon concentration 100 Bq/m 3 linked to an exposure period of 25-30 years [4]. The health risk assessment has demonstrated that radon is the second cause of cancer after smoking [1,5].…”
Section: Introductionmentioning
confidence: 97%
“…Findings from epidemiologic studies support a strong causal association between indoor radon concentration and lung cancer mortality 1 , 2 . According to combine of several studies 3 excess risk of lung cancer is about 14% per radon concentration 100 Bq/m 3 linked to an exposure period of 25–30 years. ICRP consider that there is no known threshold concentration below which radon exposure presents no risk of lung cancer 4 .…”
Section: Introductionmentioning
confidence: 99%